ASSESSMENT OF STRESS AND ANXIETY LEVELS IN PARENTS OF CHILDREN WITH CONGENITAL HEART DISEASE USING THE DASS-21 SCALE (Vietnam Journal of Community Medicine, 2026)
Objectives: To identify risk factors for stress and anxiety among parents of children with congenital heart disease.Subjects and methods: A total of 50 parents (either father or mother) and their children aged from 1 month to 15 years who were receiving treatment at the Pediatric Center of Hue Central Hospital from August 2024 to August 2025 were enrolled in the study.Results: The prevalence of anxiety and stress disorders among parents of children with congenital heart disease was 50% and 38%, respectively, with most cases classified as mild to moderate. Risk factors associated with stress disorders included parental age ≤ 30 years (OR = 4.88; 95% CI: 1.17-20.26) and having a firstborn child with congenital heart disease (OR = 6.96; 95% CI: 1.85-26.10). Child-related factors that increased the risk of parental stress were severe pneumonia (OR = 21.67; 95% CI: 4.72-99.53) and prolonged hospitalization ≥ 2 weeks (OR = 12.27; 95% CI: 2.31-65.34). A significant factor associated with increased risk of anxiety disorders in parents was having a child with cyanotic congenital heart disease (OR = 5.76; 95% CI: 1.34-24.36).Conclusions: Higher stress levels are associated with younger parental age, having a child with congenital heart disease as the firstborn, and severe pneumonia in the child, whereas cyanotic congenital heart disease is associated with an increased risk of parental anxiety.
Keywords: Congenital heart disease, stress, anxiety.